Impact of Gold Prices, Exchange Rate, BI Rate, and Inflation on the Indonesia Stock Exchange Composite Index (2020–2025) - Beryl Dani Athallah Zhahran; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of gold prices, exchange rate, BI Rate, and inflation on the Indonesia Composite Index (IHSG). The data used in this study are secondary data obtained from official publications of relevant institutions during the research period. The analytical method applied is multiple linear regression, preceded by classical assumption tests to ensure the validity and reliability of the regression model. The results indicate that partially, gold prices and inflation have a positive and significant effect on the IHSG, while the exchange rate has a significant effect on the IHSG. Meanwhile, the BI Rate does not have a significant effect on the IHSG. Simultaneously, gold prices, exchange rate, BI Rate, and inflation have a significant effect on the IHSG. These findings suggest that macroeconomic factors play an important role in influencing the movement of the capital market in Indonesia. This study is expected to provide additional insight for investors and academics in understanding the dynamics of the IHSG influenced by macroeconomic conditions.